2002
DOI: 10.1074/jbc.m107882200
|View full text |Cite
|
Sign up to set email alerts
|

Human Relaxin Gene 3 (H3) and the Equivalent Mouse Relaxin (M3) Gene

Abstract: We have identified a novel human relaxin gene, designated H3 relaxin, and an equivalent relaxin gene in the mouse from the Celera Genomics data base. Both genes encode a putative prohormone sequence incorporating the classic two-chain, three cysteine-bonded structure of the relaxin/insulin family and, importantly, contain the RXXXRXX(I/V) motif in the B-chain that is essential for relaxin receptor binding. A peptide derived from the likely proteolytic processing of the H3 relaxin prohormone sequence was synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
402
1
11

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 360 publications
(419 citation statements)
references
References 46 publications
5
402
1
11
Order By: Relevance
“…12,13 Of the 3 relaxin peptides, H2 relaxin remains the most widely studied for several reasons: 1) the availability of specific H2 relaxin antibodies 8 , 2) the significance and characterized profile of circulating H2 relaxin during pregnancy 8 and 3) the understanding that H2 relaxin retains the greatest bioactivity compared to H1 and H3. [12][13][14] PC-3 and LNCaP human prostate cancer cell lines have been employed to investigate differential H1 and H2 relaxin gene regulation, expression and transcript half-life. 12,15,16 It appears that although H1 relaxin has a greater half-life (3.17 days) compared to H2 relaxin (11.4 hours), H2 relaxin possesses stronger promoter regulation leading to greater mRNA levels and possibly higher peptide concentration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Of the 3 relaxin peptides, H2 relaxin remains the most widely studied for several reasons: 1) the availability of specific H2 relaxin antibodies 8 , 2) the significance and characterized profile of circulating H2 relaxin during pregnancy 8 and 3) the understanding that H2 relaxin retains the greatest bioactivity compared to H1 and H3. [12][13][14] PC-3 and LNCaP human prostate cancer cell lines have been employed to investigate differential H1 and H2 relaxin gene regulation, expression and transcript half-life. 12,15,16 It appears that although H1 relaxin has a greater half-life (3.17 days) compared to H2 relaxin (11.4 hours), H2 relaxin possesses stronger promoter regulation leading to greater mRNA levels and possibly higher peptide concentration.…”
mentioning
confidence: 99%
“…While H2 and H3 relaxins are expressed in a number of tissues, in males their predominant expression is found in the prostate and brain, respectively. 12,13 Of the 3 relaxin peptides, H2 relaxin remains the most widely studied for several reasons: 1) the availability of specific H2 relaxin antibodies 8 , 2) the significance and characterized profile of circulating H2 relaxin during pregnancy 8 and 3) the understanding that H2 relaxin retains the greatest bioactivity compared to H1 and H3. [12][13][14] PC-3 and LNCaP human prostate cancer cell lines have been employed to investigate differential H1 and H2 relaxin gene regulation, expression and transcript half-life.…”
mentioning
confidence: 99%
“…Like insulin, the intervening C peptide chain of relaxin-3 is removed by proteolytic processing. The relaxin-3 gene has been identified in humans (H3) [2], mice (M3) [2] and rats (R3) [3], and the gene products are highly homologous. R3 and M3 mRNA expression is localized to the nucleus incertus (NI) of the brainstem [3], a small nucleus in the central gray of the median dorsal pons near the fourth ventricle with projections to many hypothalamic nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies of the GPCR142 gene indicated that the RLN3 gene is the only member of the RLN family showing the ability to activate this gene (BATHGATE et al, 2002). The GPCR142 gene contains a single exon and is located on chromosome 1 (1q22) in human (FREDRIKSSON et al, 2003).…”
mentioning
confidence: 99%
“…Background: The RLN3 gene has been recently reported as a ligand for two related orphan G protein-coupled receptors, GPCR135 and GPCR142 (BATHGATE et al, 2002;LIU et al, 2003a;LIU et al, 2003b;CHEN et al, 2005). Pharmacological studies of the GPCR142 gene indicated that the RLN3 gene is the only member of the RLN family showing the ability to activate this gene (BATHGATE et al, 2002).…”
mentioning
confidence: 99%